(untitled) (Olhar de Professor, 2020)
This work aims presenting an analysis of a didactic script (PIETROBON, 2018) to organize the planning in the acting stage of the Supervised Internship in Childhood Education, at the Pedagogy faculty of the Universidade Estadual do Centro-Oeste, Campus Prudentópolis-PR. After finishing the acting stage, a survey was performed in a qualitative approach with 22 students. They evaluated that the didactic script used, corresponds to the needs from the institutions and the children, and they did not suggest any changes regarding the document mentioned. We noticed out that despite the didactic script has been elaborated for online learning Pedagogy courses, for its supervised internship in childhood education, it also might be used in Pedagogy traditional classes.